The singularity : could artificial intelligence really out-think us (and would we want it to?) - Awret, Uziel; Chalmers, David John, 1966- (Exeter : Imprint Academic, 2016)
This volume represents the combination of two special issues of the Journal of Consciousness Studies on the topic of the technological singularity. Could artificial intelligence really out-think us, and what would be the likely repercussions if it could? Leading authors contribute to the debate, which takes the form of a target chapter by philosopher David Chalmers, plus commentaries from the likes of Daniel Dennett, Nick Bostrom, Ray Kurzweil, Ben Goertzel, Frank Tipler, among many others. Chalmers then responds to the commentators to round off the discussion.
Jesse Prinz -- Singularity and Inevitable DoomMurray Shanahan -- Satori Before Singularity; Carl Shulman and Nick Bostrom -- How Hard is Artificial Intelligence? Evolutionary Arguments and Selection Effects; Eric Steinhart -- The Singularity: Beyond Philosophy of Mind; Burton Voorhees -- Parsing the Singularity; David J. Chalmers -- The Singularity: A Reply to Commentators; Back matter; Also available
Print version record.
"The commentaries in this volume were originally published as two special issues of the Journal of consciousness studies, vols. 19 (1-2) and 19 (7-8). The original target article was published JCS, vol. 17 (9-10)"--Title page verso
Includes bibliographical references.
eBooks on EBSCOhost
Keywords: Artificial intelligence -- Forecasting; Artificial intelligence -- Psychological aspects; Conscious automata; Technology -- Social aspects; Intelligence artificielle -- Prévision.; Intelligence artificielle -- Aspect psychologique; Machines intelligentes; COMPUTERS -- General; Artificial intelligence -- Forecasting; Conscious automata; Technology -- Social aspects